Socialising Students ? Socialising Universities. Higher Education as an Institutional Educational Environment - Nizińska, Adrianna (INSTED: Interdisciplinary Studies in Education & Society, 2012)
Demands for socializing institutions of higher education and reinforcing the social capital of students have been present in the public sphere for some time now. Reinforcing the social capital and competences connected therewith can be justified at several levels: in macro dimension this demand is imposed by standardising and unifying actions connected with European ones. In the meso (institutional) dimension the significance of social capital of students will be revealed due to changes in the organisation framework resulting from popularisation of studies. It will be also reflected in the comparison of the ratio of students attending full-time courses and those who follow extramural studies. The changes in the meso area remain closely connected with changes from the micro area, regarding psychological skills, social and cultural competences and readiness to educate ?new? students.